Fossil Neuroptera of the Lower Cretaceous of Baisa, East Siberia. Part 4: Psychopsidae. - Makarkin, Nikolai Vladimir (Beiträge zur Entomologie = Contributions to Entomology, 1997)
Baisopsychops lambkini gen. et sp. n. aus der Unteren Kreide von Baisa in Ostsibirien wird beschrieben. Nomenklatorische Handlungen lambkini Makarkin, 1997 (Baisopsychops), spec. n. Baisopsychops Makarkin, 1997 (Psychopsidae), gen. n.